Polymeric Nanomaterials as Nanomembrane Entities for Biomolecule and Drug Delivery - Albisa, Airama; Espanol, Laura; Prieto, Martin; Sebastian, Victor (Current Pharmaceutical Design, 2017)
Background: Bio-nanomaterials assembled into nanomembrane entities are actively studied to circumvent the uncontrollable list of shortcomings of conventional delivery systems: low water solubility, unfavorable stability, short circulation time in plasma, rapid clearance from the human body, poor bioavailability, non-specific toxicity against normal tissue and cells, low cellular uptake and susceptibility to enzyme degradation. Basically, these nanoentities enable to exploit the therapeutic value of many promising biomolecules and drugs (B), controlling the mass transport of B at a certain rate or even on demand if a stimulus is applied. The large surface-to-volume ratio of bio-nanomaterials as well as their tunable properties enable to increase the biocompatibility, bioavailability, solubility and permeability of many unique B which are otherwise difficult to deliver. Results: This review paper will focus on the last advances of bio-nanomaterials applied as nanomembranes in biomolecule and drug delivery, as well as their more remarkable properties and applications in biomedicine. Conclusion: New advances have been drastically established in the production of smart nanomembranes that alter their own structure and function in response to the environment. These new insights have been used for the production of smart drug delivery nanomembranes. These nanomembranes entities have the potential to revolutionize the biomedicine but there are still some shortcomings to address in order to translate the laboratory production to the clinic.
Keywords: biomaterials